Turmeric extract loaded nanoliposome as a potential antioxidant and antimicrobial nanocarrier for food applications. (June 2019) - Karimi, Nayyer; Ghanbarzadeh, Babak; Hajibonabi, Farid; Hojabri, Zoya; Ganbarov, Khudaverdi; Kafil, Hossein Samadi; Hamishehkar, Hamed; Yousefi, Mehdi; Mokarram, Reza Rezaei; Kamounah, Fadhil S.; Yousefi, Bahman; Moaddab, Seyyed Reza
Abstract: Antioxidant and antimicrobial activities of turmeric extract loaded nanoliposomes (TEL) and their potential application in drinks as functional foods were evaluated. The TEL were prepared using a thin layer hydration method coupled with high shear homogenization and sonication. The average size, polydispersity index, zeta potential, encapsulation efficiency and loading capacity of the TEL were determined. The TEL were almost physically constant over 40 days at room temperature. Scanning electron microscopy analysis showed the homogeneous size of the TEL. The turmeric extract released in a drink model with pH = 6.8 was significantly lower than that with pH = 3.5 and 4.5 (P ≤ 0.05). Moreover, Fourier transform infrared spectra (FTIR) indicated interactions of the turmeric extract with phospholipid groups in the nanoliposome structures. Antioxidant activity of the TEL were significantly higher (P ≤ 0.05) than that of a free extract. Microbiological tests showed that the TEL had higher inhibitory activity than the free turmeric extract. The results showed that the TEL may be a suitable system for designing functional foods containing nanocarriers. Graphical abstract: Image 1 Highlights: TEL were prepared using thin layer hydration coupled with high shear homogenization and sonication. Antioxidant activity of TEL was significantly higher than free extract. Microbiological tests showed that TEL had higher activity than free turmeric extract. TEL was a suitable system for designing functional foods containing nanocarriers.